Assessing the Risk of Stress in Organizations: Getting the Measure of Organizational-Level Stressors - Wood, Stephen; Ghezzi, Valerio; Barbaranelli, Claudio; Di Tecco, Cristina; Fida, Roberta; Farnese, Maria Luisa; Ronchetti, Matteo; Iavicoli, Sergio (Frontiers in Psychology, 2019)
Great Britain’s Health and Safety Executive (HSE) developed the Management Standards Indicator Tool to help organizations to assess and monitor organizational risks of work-related stress through surveying employees about the psychosocial risks for stress in their jobs. The use of employee-level data for deriving an organizational-level measure of psychosocial risks assumes that the constructs have equivalent meanings at different levels. However, this isomorphic condition has never been tested and this study fills this gap. Using data collected by the Italian Workers’ Compensation Authority (INAIL) from 66,188 employees nested in 775 organizations, we demonstrate that the organizational-level measure representing the seven dimensions of the Management Standards Indicator Tool is equivalent, though not identical, to the individual-level measure. This implies that the organizational level is not a mirror of the aggregation of the individual level, and that the risk of work-related stress in an organization may derive not simply from bottom-up processes, but may be generated by top-down influences (e.g., organizational policies). Interventions may then be meaningfully targeted at the organizational level in the expectation that they will reduce the risk of work-related stress among the entire workforce, the valid measurement of which can be performed through the HSE’s Management Standards Indicator Tool.